2018
DOI: 10.1007/s12264-018-0250-6
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Effective Connectivity of the Anterior Forebrain Regions in Disorders of Consciousness

Abstract: A number of studies have indicated that disorders of consciousness result from multifocal injuries as well as from the impaired functional and anatomical connectivity between various anterior forebrain regions. However, the specific causal mechanism linking these regions remains unclear. In this study, we used spectral dynamic causal modeling to assess how the effective connections (ECs) between various regions differ between individuals. Next, we used connectome-based predictive modeling to evaluate the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…In line with our structural findings, dynamic causal modelling (DCM) provided support to the PCC's role in mediating functional disconnections in the DMN in PDOC [6]. Similarly, a recent study demonstrated abnormal effective connectivity in anterior forebrain regions in PDOC [29]. Here, we expand these results by using DCM to investigate causal dynamics within and between regions of the DMN and AFM in a group of PDOC patients, including both diagnoses of vegetative and minimally conscious state.…”
Section: Introductionsupporting
confidence: 79%
“…In line with our structural findings, dynamic causal modelling (DCM) provided support to the PCC's role in mediating functional disconnections in the DMN in PDOC [6]. Similarly, a recent study demonstrated abnormal effective connectivity in anterior forebrain regions in PDOC [29]. Here, we expand these results by using DCM to investigate causal dynamics within and between regions of the DMN and AFM in a group of PDOC patients, including both diagnoses of vegetative and minimally conscious state.…”
Section: Introductionsupporting
confidence: 79%
“…EC depends on the mechanism of the causal effects that generated from the data, which can reflect the specific strength and direction of interaction information in the brain region ( Stephan and Friston, 2010 ). Some researchers began to apply EC to fMRI analysis ( Sharaev et al, 2016 ; Wang et al, 2016 ; Park et al, 2017 ; Chen et al, 2018 ; Ma et al, 2018 ). EC can be analyzed by various methods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the abnormal functional interactions of precuneus in DOC patients by using either static FC ( Qin et al, 2015 , Stender et al, 2014 , Wu et al, 2019 ) or dynamic FC ( Cao et al, 2019 , Luppi et al, 2019 ). Several recent dynamic causal modelling (DCM) studies ( Chen et al, 2018a , Crone et al, 2017 , Crone et al, 2015 ) also found the disrupted effective connectivity between PCC/precuneus and other regions (e.g., medial frontal cortex, inferior parietal lobule, and globus pallidus) in DOC patients, reflecting the abnormal information flow related to precuneus at ROI level.…”
Section: Discussionmentioning
confidence: 95%